INTERAKSI SOSIAL REMAJA PEMAIN GAME ONLINE MOBILE LEGENDS DENGAN TEMAN SEBAYA DI DESA INDRASARI KECAMATAN MARTAPURA - Mattiro, Syahlan; Rahman, Zaur; Widaty, Cucu (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This research aims to find: (1) the forms of social interaction that occur among teenagers who play the online game Mobile Legends with their peers (2) the reasons why teenagers are interested in playing the online game Mobile Legends with their peers. The research method used in this study is a qualitative method. The selected research source is purposive sampling with 4 informants. Data collection techniques were carried out using participant observation techniques, interviews and documentation. The data analysis used uses data reduction, data display and verification steps. Testing the validity of the data used is source triangulation and technical triangulation and using reference materials. The results of the research found that (1) there are 4 forms of social interaction among teenagers playing mobile legends, namely Cooperation, Competition, Conflict and Accommodation (2) the reasons why teenagers are interested in playing mobile legends are 1) Motive Purpose (in order to motive) is the reason for playing games to fill free time and as entertainment. 2) Because Motive, namely, the reason for being interested in playing games is because many friends play mobile legends and the development of mobile legends games is increasingly interesting. Based on the results of this research, it is recommended that Mobile Legends online game players are advised not to become too addicted to playing Mobile Legends, especially for those who are still studying, it would be better to prioritize education before playing Mobile Legends. Students and the public are advised to know that the Mobile Legends online game does not always have a bad impact on life. Because from mobile legends game we can learn how to build cooperation between players, which can strengthen their social ties.